DAMPAK MEDIA SOSIAL TERHADAP POLA INTERAKSI SOSIAL BUDAYA SISWA DI SEKOLAH SDN 01 DESA TERUSAN MENANG SP PADANG KABUPATEN OGAN KOMERING ILIR - Fatimatuzzahra, Fatimatuzzahra; Juliana, Siti Arbaina; Riyani, Roja (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Social media is a social interaction between individuals in sharing and exchanging information. Social media can include various ideas, opinions, notions and content in virtual communities and is able to present and translate new ways of communicating with technology that is completely different from traditional media (Watson, 2009). The development of the increasingly innovative world of technology in the global era has had a direct impact on society, especially the younger generation. The term social media is composed of two words, namely